الحاجات الارشادية لتلاميذ المرحلة المتوسطة - قاسمي، هاجر (جامعة الوادي university of Eloued, 2019)
الملخص: تتناول الدراسة الحاجات الإرشادية لدى تلاميذ سنة الرابعة متوسط , وقد هدفت الدراسة إلى معرفة طبيعة الحاجات الإرشادية لتلاميذ السنة الرابعة متوسط و معرفة الفروق بين التلاميذ في حاجاتهم التربوية و الاجتماعية و الانفعالية و الجسمية في ضوء متغيري الجنس و المستوى الدراسي . وقد تحددت الدراسة الحالية بالمنهج الوصفي المعتمد على الاستكشاف الملائم لطبيعة دراستنا الحالية , وقد اختيرت العينة بالطريقة العشوائية البسيطة من متوسطة محمد شعباني و معروفي الطاهر و متوسطة جعفري يوسف ببلدية جامعة ولاية الوادي , وقد شملت عينة الدراسة ( 150) تلميذ وتلميذة . وكانت الأساليب الإحصائية المستخدمة مقتصرة على اختبار " ت" و النسبة المئوية والانحراف المعياري و المتوسط الحسابي , تحليل التباين , معامل ألفا كرونباخ , وسبيرمان براون , بيرسون , أما أداة القياس تمثلت في مقياس الحاجات الإرشادية . وقد توصلت دراستنا إلى النتائج التالية: - ترتيب الحاجات الإرشادية حسب أفراد عينة الدراسة و التي كانت كالتالي ( الحاجات الدراسية, الحاجات الاجتماعية, الحاجات الانفعالية, الحاجات الجسمية ). - لا توجد فروق ذات دلالة إحصائية في الحاجات الإرشادية حسب الجنس لدى تلاميذ السنة الرابعة متوسط. - لا توجد فروق ذات دلالة إحصائية في الحاجات الإرشادية حسب المستوى الدراسي لدى تلاميذ السنة الرابعة متوسط. وقد تم تفسير نتائج هذه الدراسة في ضوء الجانب النظري بالإضافة إلى الواقع الميداني وختمت الدراسة ببعض الاقتراحات و التوصيات الموجهة للمهتمين بمجال الإرشاد والتوجيه لدى فئة المتمدرسين في السنة الرابعة متوسط . Having food studying " Needs guidelines l have students middle school " has been targeted students to me know the nature of extension needs for students fourth middle year and to know the differences between students in their educational , social , emotional and physical needs In the light of the variables of sex and level of study The present study has been determined by a decretive approach based on appropriate exploration of the nature of our current stuaty ,the sample was chosen in a simple random way from the medium of colonel Mohammed chaabani, maaroufieltaher and jafariyoussef , state of the valley ,the sample included(150) students and students. The statistical methods used were limited to the "T text ",the percentage, the standard deviation and the arithmetic mean ,the variance analysis, and the cronbach, spearman, brown, and Pearson, the study instrument was a questionnaire. Our study found the following results: 1- The educational needs were followed by social needs, emotional needs, andphysical needs. 2- There were no statistically significant differences in extension needs by sex among fourth year students. 3- There were no statistically significant differesin educational needs by level of study among fourth , year students. The results of this study were explained in the light of the theoretical side as well as the field reality . The study ended with some suggestions and recommendations addressed to those interested in guidance and guidance in the group of teachers.
دراسة ميدانية لتلاميذ السنة الرابعة متوسط ببلدية جامعة
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الحاجات الإرشادية، الإرشاد النفسي; Besoins en conseil, conseil psychologique; Counseling needs, psychological counseling